The Influence of Tourist Facilities and Attractions on Visitor Satisfaction at Toba Caldera Resort Pardamean Sibisa - Pasaribu, Tryadevy; Haro, Jamardua (CV. Civiliza Publishing, 2025)
The development of tourist destinations in Indonesia, particularly the Lake Toba area, is a major focus in supporting the tourism sector and the MICE (Meeting, Incentive, Convention, Exhibition) industry. Toba Caldera Resort, managed by the Lake Toba Authority, plays a crucial role as a leading destination in attracting tourists. This research is motivated by the importance of understanding the factors that influence visitor satisfaction as an indicator of successful destination management. The purpose of this research is to determine the extent to which tourist facilities and attractions influence visitor satisfaction at Toba Caldera Resort. This research uses a quantitative method with an associative approach. A sample of 100 respondents was selected using an accidental sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression. The results show that both facilities and tourist attractions have a positive and significant effect on visitor satisfaction, both partially and simultaneously. The conclusion of this research is that facilities and tourist attractions are the main factors determining the level of visitor satisfaction at Toba Caldera Resort. The better the quality of the facilities and the more attractive the attractions offered, the higher the level of perceived satisfaction. Therefore, the management and development of these two aspects must be prioritized in strategies to increase the attractiveness and sustainability of tourist destinations.